Continuation power flow for voltage stability assessment / Mohd Zamri Laton - Laton, Mohd Zamri (2006)
This thesis presents a potential algorithm for continuation power flow in order to find a power flow solution at its bifurcation point. The conventional Newton's method was found to be inadequate to obtain the maximum loading point (MLP) or critical point of the power system due to the Jacobian matrix singularity. This problem can be solved by using continuation power flow, which remains well condition at the saddle node bifurcation point due to the divergence at this point is eliminated. The continuation power flow program is developed using MATLAB programming language base on algorithm of continuation power flow (CPF) technique, which can compute efficiently the parameter at saddle node bifurcation point. The existing continuation power flow (CPF) technique base on predictor-corrector method is the most accurate method but very time consuming. Thus a new technique is implemented in this paper in order to reduce the time consuming faced by the existing method. A small test system is used for the implementation of this technique and another medium test system is also used for verification of the program used.